SOCIAL INNOVATION PROJECT “BUSINESS SKILLS DEVELOPMENT AND BUSINESS OPPORTUNITIES AWARENESS PROGRAM FOR FAMILY WELFARE EDUCATION IN KAMPUNG KEDUNG KLINTER” - DAVINA CHRISTY; SHERLEEN GIANINA; AURELIA YOHANA; GIOVANI HOKINI (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This social innovation project unfolds as the "Business Skills Development and Business Opportunities Awareness Program for Family Welfare Education in Kampung Kedung Klinter," aiming to address specific community challenges while catalyzing economic growth at the family level. Focused on imparting bento-making skills, the initiative takes a holistic approach, encompassing entrepreneurship fundamentals, financial literacy, and market awareness. Through collaborative efforts and targeted training sessions, the program not only equips participants with practical business skills but also cultivates an entrepreneurial mindset. Anticipated outcomes include increased family income, women's empowerment, and overall economic development within the community. This innovative project highlights the potential for positive societal impact by blending traditional practices with contemporary business strategies, contributing to sustained socio-economic growth.